Catheter-related infection and thrombosis of the internal jugular vein in hematologic-oncologic patients undergoing chemotherapy: a prospective comparison of silver-coated and uncoated catheters - Harter, Christoph; Salwender, Hans; Bach, Alfons; Egerer, Gerlinde; Goldschmidt, Hartmut; Ho, Anthony Dick (Cancer, 2002)
BACKGROUND Catheter-related venous thrombosis is one of the most frequent complications of central venous catheters (CVCs). This complication occurs in 4- 40% of patients with hematologic malignancies receiving conventional chemotherapy after placement of CVCs. METHODS The objective of this prospective study was to assess whether a silver-coated CVC poses an additional risk in the development of catheter-related thrombosis in hematologic-oncologic patients. Patients were randomized to receive either silver-coated polyurethane catheters (BactiGuard; Metacot, Stockholm, Sweden) or uncoated standard polyurethane catheters (Cavatheter, Fresenius AG, Bad Homburg, Germany) for central venous access. Silver-coated catheters (n = 120) and standard catheters (n = 113) were inserted into the jugular vein in 233 consecutive patients. Variables that may be significant for the development of thrombosis were comparable in the two groups. After removal of the CVC, the patency of both jugularian veins internal as well as external was assessed with real-time ultrasound (Sonolayer-SAL-35A; Toshiba, Tokyo, Japan). RESULTS Four of 233 patients (1.5%) were found to have venous thrombosis. Incomplete occlusion of the internal jugular vein occurred in 2 patients (0.75%, parietal thrombosis), and complete thrombosis, although clinically silent, was found in 2 patients (0.75%). There was no difference between patients with silver-coated and uncoated CVCs. CONCLUSIONS The authors concluded that this novel silver-coated CVC does not cause a higher rate of central venous thrombosis compared with standard CVCs. The low overall incidence of central venous thrombosis might be attributed to the routine application of low-dose heparin in our patients during chemotherapeutic treatment. Cancer 2002;94:245-51. © 2002 American Cancer Society.